The Determinant of Whistleblowing Intention in the Case of Bank Fraud - Nanang Shonhadji (Binus Business Review, 2021)
Banking transactions in Indonesia have experienced very rapid development in line with the need for financing in the real sector. However, along with this rapid development, fraud is still a classic problem in the banking sector. The research aimed to empirically prove the effect of professional commitment, moral courage, idealism, and altruistic values on the intention to do whistleblowing. In addition, the research also investigated whether the locus of control was a variable that moderated the relationship. A quantitative research method using questionnaire instruments was used for data collection. The population was all employees of banks operating in Surabaya. The research sample included the employees of national private banks operating in Surabaya. The data analysis technique was the path analysis test with the WarpPLS program. The results show that professional commitment, moral courage, and idealism have a significant effect on the intention to do whistleblowing. Meanwhile, altruistic values do not affect the intention to do whistleblowing. The results also indicate that locus of control is a moderating variable that strengthens the relationship of professional commitment, moral courage, and idealism in affecting the intention to do whistleblowing. Professional commitment, moral courage, and idealism have become strong awareness for bank employees to participate in eradicating corruption, white-collar crime, and all forms of fraud in the organizational environment.